A new species of Capnia (Plecoptera: Capniidae) from China - Li, Weihai; Kong, Fanbin; Yang, Ding (Zootaxa, 2011)
A new species of the genus Capnia, Capnia yunnana sp. nov., is described as new to science from Yunnan Province, Southwestern China. Its relationship with closely related species is discussed.